Eupholidoptera stelae sp. nov. a new bush-cricket from Cyprus (Orthoptera: Tettigoniidae) - Willemse, Luc; Makris, Christodoulos; Odé, Baudewijn (Zootaxa, 2025)
A small, rather secretive new species of Eupholidoptera, E. stelae sp. nov. (Tettigoniidae, Tettigoniinae, Pholidopterini) from the Troodos Massif in Cyprus is described. The intra- and infra-generic assignment is discussed in detail.